2001
DOI: 10.1139/h01-029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Creatine Monohydrate Supplementation During Combined Strength and High Intensity Rowing Training on Performance

Abstract: This study investigated the effect of creatine monohydrate (Cr) supplementation on performance and training volume in rowers. Twenty-two rowers trained with continuous and interval rowing and resistance training 4 and 2 days/week, respectively, for 6 weeks. Cr supplementation consisted of a 5-day load (0.3 g/kg(-1) x day(-1)) followed by a 5-week maintenance dose (0.03 g/kg(-1) x day(-1)) while training. Five days of Cr loading did not change body composition, repeated interval rowing performance, 2,000-m rowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 0 publications
2
23
0
1
Order By: Relevance
“…Creatine has been investigated in a few studies with reports of both unchanged (Burke et al, 1996; Mujika et al, 1996; Syrotuik et al, 2001; De Andrade Nemezio et al, 2015) and improved performance (Rossiter et al, 1996; McNaughton et al, 1998). Importantly the majority of these studies reported mean power from ergometers (Rossiter et al, 1996; McNaughton et al, 1998; Syrotuik et al, 2001; De Andrade Nemezio et al, 2015) but for athletes in which body mass often is a concern it is important to account for any increase in weight which is common with creatine supplementation (Mujika et al, 1996; McNaughton et al, 1998; De Andrade Nemezio et al, 2015). Accordingly, an increased body weight will increase resistive forces on an athlete during forward propulsion leading to a higher energy expenditure for a given speed especially during running (LeCheminant et al, 2009) and in the water (Mujika et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Creatine has been investigated in a few studies with reports of both unchanged (Burke et al, 1996; Mujika et al, 1996; Syrotuik et al, 2001; De Andrade Nemezio et al, 2015) and improved performance (Rossiter et al, 1996; McNaughton et al, 1998). Importantly the majority of these studies reported mean power from ergometers (Rossiter et al, 1996; McNaughton et al, 1998; Syrotuik et al, 2001; De Andrade Nemezio et al, 2015) but for athletes in which body mass often is a concern it is important to account for any increase in weight which is common with creatine supplementation (Mujika et al, 1996; McNaughton et al, 1998; De Andrade Nemezio et al, 2015). Accordingly, an increased body weight will increase resistive forces on an athlete during forward propulsion leading to a higher energy expenditure for a given speed especially during running (LeCheminant et al, 2009) and in the water (Mujika et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A multiple repetition maximum (mRM) strength assessment was completed for bilateral leg press at a 458 incline and supine bench press exercises, as previously described for our laboratory [30]. Multiple RM strength test protocols have been shown to accurately predict 1 RM in our laboratory [31].…”
Section: Multiple Repetition Maximum Testingmentioning
confidence: 99%
“…Since many team sports, such as football, basketball, hockey and soccer utilize repeated bouts of short sprints separated by active recovery periods, interval running may be applicable to many sports and sensitive to nutritional supplements that are designed to delay high-intensity, exercise-induced fatigue. In fact, evidence exists to support the use of high-intensity interval training (HIIT) strategies to improve performance [7], however, only a few studies have examined HIIT combined with nutritional supplementation [8-13]. …”
Section: Introductionmentioning
confidence: 99%